Clinician Engagement in Quality: A Literature Review. Issue 1 (January 2021) - Dickinson, Marie; Duffield, Christine; Bichel-Findlay, Jen; Travaglia, Joanne
Abstract : Background and Objectives: Defining quality in the health care context has proven difficult, with many organizations not able to clearly articulate their use of this term in a manner that is easily understood by their clinical staff. This review seeks to investigate the literature to explore clinician engagement in quality including where engagement has been problematic, and if the reasons for this have been identified. Methods: An integrative review of the literature was undertaken to determine whether evidence within the literature supports a hypothesis that there is a lack of understanding of and engagement in quality at an organizational level by health professionals. A search of the literature was conducted using EBSCO Academic Complete, CINAHL, and MEDLINE databases. Results: This article identified 18 studies where the understanding of quality by clinicians and their level of engagement with the process are investigated. We found that there has been no comprehensive study that explores the development of an agreed-upon definition and measurement of quality or clinician understanding and engagement in quality. The studies conducted have been small and discipline-specific. Conclusion: There is a growing body of evidence indicating that clinical and nonclinical staff interpret the meaning of quality and quality improvement differently. Quality and quality improvement are interpreted in relation to the clinician's individual work, professional, and learning and development experience. The literature suggests that clinician interpretation is influenced in part by their own personal beliefs and values, in addition to their interpretation of their individual work/professional responsibilities.